2021
DOI: 10.1002/anie.202104520
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Elucidation of Bisdibenzocorannulene in Multiple Redox States

Abstract: We report an anti-folded bowl-shaped bisdibenzocorannulene (BDBC)f eaturing an ew chair-cyclohexane-like hexagon as abridge of two dibenzocorannulene moieties.The neutral compound showed multiple redox-active properties and could be converted to the corresponding redox states through chemical reduction or oxidation.C hemical reduction of BDBC by stoichiometric addition of metallic potassium in the presence of [18]crown-6 ether,p rovided ar adical anion BDBCC À and adianion BDBC 2À ,respectively;while chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 75 publications
(23 reference statements)
0
18
0
Order By: Relevance
“…In addition, delocalization of a charge over an extended π‐conjugation is effective for the synthesis and isolation of charged species as stable entities with carbon‐centered ions. Indeed, aromatic hydrocarbons are known to exhibit unique electrochemical and spectroscopic properties based on their π‐conjugated systems, and several systems capable of redox interconversion between neutral and cationic (anionic) states have been reported by effectively stabilizing the charged state by embedding heteroatoms or introducing heteroatom‐substituents into the π‐skeleton [21–32] . On the other hand, since it is difficult to stabilize such charged species without heteroatoms, the development of pure hydrocarbon‐based redox systems is challenging from the viewpoint of the stability of cationic (anionic) species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, delocalization of a charge over an extended π‐conjugation is effective for the synthesis and isolation of charged species as stable entities with carbon‐centered ions. Indeed, aromatic hydrocarbons are known to exhibit unique electrochemical and spectroscopic properties based on their π‐conjugated systems, and several systems capable of redox interconversion between neutral and cationic (anionic) states have been reported by effectively stabilizing the charged state by embedding heteroatoms or introducing heteroatom‐substituents into the π‐skeleton [21–32] . On the other hand, since it is difficult to stabilize such charged species without heteroatoms, the development of pure hydrocarbon‐based redox systems is challenging from the viewpoint of the stability of cationic (anionic) species.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, aromatic hydrocarbons are known to exhibit unique electrochemical and spectroscopic properties based on their π-conjugated systems, and several systems capable of redox interconversion between neutral and cationic (anionic) states have been reported by effectively stabilizing the charged state by embedding heteroatoms or introducing heteroatom-substituents into the π-skeleton. [21][22][23][24][25][26][27][28][29][30][31][32] On the other hand, since it is difficult to stabilize such charged species without heteroatoms, the development of pure hydrocarbonbased redox systems is challenging from the viewpoint of the stability of cationic (anionic) species. In general, even though the incorporation of heteroatoms is an effective method for stabilizing charged species and modulating the electronic properties of organic molecules, the potential instability of bonds between carbon and heteroatoms in the neutral state may reduce fatigue resistance in organic electronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, molecules of 1 adopt antiand syn-geometries depending on the conformation of each corannulene unit. 7,32 Zero-point-corrected energy values from DFT simulations under vacuum predict a negligible energy difference between the conformers (0.1 kcal mol −1 ). A variabletemperature (VT) 1 H NMR spectroscopic study of 1 in CD 2 Cl 2 from −90 °C to 20 °C showed that the peak intensities weaken upon lowering the temperature (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1b). 27,32 Various interaction modes are expected for both geometries, including interdigitated structures, parallel-stacked structures, and stacked structures with a lateral shift (Fig. 1c).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation